The development of business continuity plan for online delivery: a case study in Malaysian private higher learning institution - Hassan, Nurhanim; Leong, Lim Chee; Md Isa, Filzah (American Scientific Publishers, 2018)
Class cancellation due to the unplanned disaster such as haze may cost private higher learning institutions a huge cost. Their reputation may also be at risk. Realizing this one of the private higher learning institutions in Malaysia has taken measures to ensure the classroom continuity despite the disruption. It captures the measures taken in dealing with classroom continuity during the event of crisis. A model of classroom continuity the event of unplanned disruption is developed for reference by other universities in developing a sustainable and cost effective Business Continuity Plan for Curriculum.